STRESS LEVELS AND COPING MECHANISMS IN FAMILIES OF PEOPLE WITH MENTAL DISORDER - Lusfin Lusfin; Nurlaila Fitriani (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2026)
Introduction: Mental disorders affect individuals mentally, emotionally, and socially, with families often serving as the primary caregivers responsible for patient care. This role frequently induces stress in families due to stigma, financial burdens, and role changes. Unmanaged stress can negatively impact both patient care and family well-being. Effective coping strategies are crucial to help families manage stress. However, research on the stress levels and coping mechanisms of families of individuals with mental disorders in South Sulawesi, particularly in Makassar, remains limited. Method: This study used a descriptive quantitative method. The instruments used include the Perceived Stress Scale and Brief Cope questionnaire. The sample for this study consisted of 210 respondents selected through purposive sampling. The data were analyzed using SPSS version 26. Results: The results of this study show that the majority of respondents are in the adult age group (19–59 years), with most being female (73.8%). The largest proportion of respondents are from the Bugis ethnic group (41%) and are Muslim (91%). Most respondents have a high school education (44.3%), are unemployed (46.7%), and are married (71%). The majority of respondents have an income below the regional minimum wage (Rp 3,642,321). The relationship of respondents to the patients with mental disorders is mostly that of a mother (29.5%), with most respondents living with the patient (84.8%) and using BPJS as the payment method (86.7%). The average duration of the family member's mental disorder is 8.1 years. The stress level experienced by families of patients with mental disorders is mostly moderate (84.8%), followed by mild stress (14.3%) and severe stress (1%). All respondents use adaptive coping mechanisms (100%). Conclusions: the majority of families of patients with mental disorders at RSKD Dadi experience a moderate level of stress, with all respondents using adaptive coping mechanisms. Future research is recommended to use more comprehensive data collection methods, such as in-depth interviews and observations, to gain a deeper understanding of the experiences of families in caring for patients with mental disorders